Reusable and Reconfigurable Material Concepts for Post-Disaster Temporary Modular Shelters: A Systematic Review From An Environmental Sustainability Perspective - Sely Novita Sari; Sarwidi; Fitri Nugraheni; Albani Musyafa (International Journal of Hydrological and Environmental for Sustainability, 2026)
Post-disaster temporary shelters in Indonesia often generate significant construction waste because of their single-use nature. This study aims to map reusable and reconfigurable concepts as the foundation of Temporary Modular Shelter (TMS) material design and to analyse their contributions to environmental sustainability. A Systematic Literature Review (SLR) following the PRISMA 2020 protocol was conducted on peer-reviewed articles and indexed proceedings published between 2015 and 2025, retrieved from Scopus, ScienceDirect, and Google Scholar. Of 412 records initially identified, 87 peer-reviewed studies met the inclusion criteria. Thematic analysis was performed using NVivo 12 with a hybrid deductive–inductive coding approach. The findings show that reusable–reconfigurable principles are operationalised through modular systems and reversible dry connections that allow shelter components to be potentially reused or adapted for permanent housing construction. Five main material components were identified: frames, wall panels, roofs, flexible elements, and flooring/base modules. The approach is reported in the reviewed literature to support construction waste reduction, circular economy practices, lower embodied carbon, and improved resource efficiency, although the magnitude of these benefits varies with material type, transport distance, and the number of reuse cycles. This study contributes an integrative sustainability-based framework linking reusable–reconfigurable principles with post-disaster TMS material systems. Remaining challenges include module standardisation, local human resource capacity, comprehensive Life Cycle Cost analysis, and socio-economic integration. The framework provides a reference for policymakers, researchers, and practitioners developing adaptive and sustainable temporary housing in disaster-prone regions.